Preparation and properties of war gases - Acharya, H. K. (Defence Science Journal, 2014)
The preparation and properties of the most important war gases which were largely used in the field during World War I are briefly reviewed. Technical and tactical aspects of these gases, and methods of their detection and decontamination have been stressed.